2018
DOI: 10.1159/000495753
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Digital Breast Tomosynthesis and Digital Mammography for Detection of Breast Cancer in Kuwaiti Women

Abstract: Objective: To investigate the sensitivity and specificity of digital mammography (DM) and digital breast tomosynthesis (DBT) for the detection of breast cancer in comparison to histopathology findings. Subjects and Methods: We included 65 breast lesions in 58 women, each detected by two diagnostic mammography techniques – DM and DBT using Senographe Essential (GE Healthcare, Buc, France) – and subsequently confirmed by histopathology. The Breast Imaging Reporting and Data System was used for characterizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our results were comparable with Bian et al [25] and Asbeutah et al [26] where they also found that DBT showed increased sensitivity and specificity compared to mammography in dense breasts. Phi et al [27] performed a meta-analysis on DBT in dense breasts for screening or diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were comparable with Bian et al [25] and Asbeutah et al [26] where they also found that DBT showed increased sensitivity and specificity compared to mammography in dense breasts. Phi et al [27] performed a meta-analysis on DBT in dense breasts for screening or diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…Phi et al [10] and Asbeutah et al [16] performed a meta-analysis on tomosynthesis in dense breasts for screening and diagnosis. They concluded that DBT increased sensitivity and the cancer detection rate in screening and diagnosis in comparison to mammography alone.…”
Section: Discussionmentioning
confidence: 99%
“…DBT has been implemented as a diagnostic tool rather than a screening technique for the past six years in our country and for many years in some parts of the world 9 . A previously published research paper 10 concluded that the translation of this technology may impact clinically by early detection of a breast lesion and further improvement in patient management, whether used for screening or diagnostic purposes. However, limited work has been published on radiation doses from DBT or a combination of DBT and FFDM for a range of clinically relevant mammographic parameters 11–14 .…”
Section: Introductionmentioning
confidence: 99%